The Causal Effect of Trust - Björn Bartling; Ernst Fehr; David B. Huffman; Nick Netzer (Institute of Labor Economics (IZA), 2018)
Trust affects almost all human relationships – in families, organizations, markets and politics. However, identifying the conditions under which trust, defined as people's beliefs in the trustworthiness of others, has a causal effect on the efficiency of human interactions has proven to be difficult. We show experimentally and theoretically that trust indeed has a causal effect. The duration of the effect depends, however, on whether initial trust variations are supported by multiple equilibria. We study a repeated principal-agent game with multiple equilibria and document empirically that an efficient equilibrium is selected if principals believe that agents are trustworthy, while players coordinate on an inefficient equilibrium if principals believe that agents are untrustworthy. Yet, if we change the institutional environment such that there is a unique equilibrium, initial variations in trust have short-run effects only. Moreover, if we weaken contract enforcement in the latter environment, exogenous variations in trust do not even have a short-run effect. The institutional environment thus appears to be key for whether trust has causal effects and whether the effects are transient or persistent.
Keywords: C91; D02; D91; E02; 330; trust; causality; equilibrium selection; belief distortions; incomplete contracts; screening; institutions